Zinc layered hydroxide-salicylate nanohybrid and its effect on Vero3 cells viability. - Ramli, Munirah; Hussein, Mohd Zobir; Mohd Yusoff, Khatijah
A new layered organic-inorganic nanohybrid based on zinc layered hydroxide (ZLH) which contains an anti-inflammatory agent, salicylate (SA) was synthesized through direct reaction of salicylic acid at various concentrations with commercially available zinc oxide (ZnO). Power x-ray diffraction (PXRD) patterns revealed that the basal spacing of the pure phase nanohybrid was 15.73 A. The SA anions were arranged in a vertical bilayer form, with the carboxylate functional groups pointing towards the inorganic layers of ZLH. Fouri er transform infrared (FTIR) spectrum for the synthesized nanohybrid illustrate ba'nds characteristic of salicylate and ZLH, thereby further confirming its intercalation into the interlayers of ZLH. The loading of SA in the nanohybrid was estimated to be around 29.7%, and the nanohybrid exhibited the properties of a mesoporous-type material. Thermogravimetry and differential thermogravimetry analyses showed that the thermal stability of the SA in the nanohybrid was greatly enhanced compared to its counterpart. In vitro cytotoxicity assay revealed that free SA, pure ZnO and the nanohybrid have mild effect on Viability of African green monkey kidney (Vero3) ceils.